2017
DOI: 10.3906/mat-1602-38
|View full text |Cite
|
Sign up to set email alerts
|

Finite volume approximation of the relativistic Burgers equation on a Schwarzschild--(anti-)de Sitter spacetime

Abstract: The relativistic versions of Burgers equations on the Schwarzschild, FLRW, and de Sitter backgrounds have recently been derived and analyzed numerically via finite volume approximation based on the concerned models. In this work, we derive the relativistic Burgers equation on a Schwarzschild-(anti-)de Sitter spacetime and introduce a secondorder Godunov-type finite volume scheme for the approximation of discontinuous solutions to the model of interest. The effect of the cosmological constant is also taken into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(30 reference statements)
0
5
0
2
Order By: Relevance
“…(3.12) becomes the viscous Burgers equation, valid for a dissipative system, where ν is a diffusion coefficient. It must also be mentioned that the Burgers equation is found in other relativistic solutions as well, such as FLRW cosmology and Schwarzschild background [17]. Based on Eq.…”
Section: Discussionmentioning
confidence: 99%
“…(3.12) becomes the viscous Burgers equation, valid for a dissipative system, where ν is a diffusion coefficient. It must also be mentioned that the Burgers equation is found in other relativistic solutions as well, such as FLRW cosmology and Schwarzschild background [17]. Based on Eq.…”
Section: Discussionmentioning
confidence: 99%
“…For the perfect fluid EMT solutions we found that two out of four subcases turn out to be the dust solution of Ref. [19] where both the matter density and the pressure vanish, but the Burgers equation also appears as a result of the solutions of the Einstein equations [29][30][31]. Two other subcases, however, indicate that warp speeds are possible with positive matter density, but at the cost of a complex solution for the warp metric regulating function.…”
Section: Introductionmentioning
confidence: 96%
“…(4.12) becomes the viscous Burgers equation, valid for a dissipative system, where ν is a diffusion coefficient. It must also be mentioned that the Burgers equation is found in other relativistic solutions, such as FLRW cosmology and the Schwarzschild background[17][18][19]. Based on Eq.…”
mentioning
confidence: 99%